2007
DOI: 10.1080/14992020701481706
|View full text |Cite
|
Sign up to set email alerts
|

Call for calibration standard for newborn screening using auditory brainstem responses

Abstract: The mode of stimulation employed in newborn screening of the auditory brainstem response has evolved from the clinically standardized supraaural earphone to the tubal insert earphone, to most recently a circumaural earphone developed for this test. Considered here is the need to develop a standard for calibration of such devices for newborn screening applications, in particular. At risk is the prospect of missing the milder degrees of hearing loss, assuming a goal of detecting all clinically-significant congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Thus, the actual level of the test signal may vary appreciably among infants regardless of the audiometric hearing level in dB nHL referenced as the pass-fail criterion level by the manufacturer. 29,30 This is particularly concerning because the stimulus will frequently be higher, with the potential result of infants with UHL or MBHL being missed.…”
Section: Screening For Uhl and Mbhl During The Newborn Periodmentioning
confidence: 99%
“…Thus, the actual level of the test signal may vary appreciably among infants regardless of the audiometric hearing level in dB nHL referenced as the pass-fail criterion level by the manufacturer. 29,30 This is particularly concerning because the stimulus will frequently be higher, with the potential result of infants with UHL or MBHL being missed.…”
Section: Screening For Uhl and Mbhl During The Newborn Periodmentioning
confidence: 99%
“…In this study, all the parameters are found to be slightly higher in the right ear which may be due to failure of the transducer of the right earphone to produce the same output level as in the left ear which may be a manufacturing defect [23].…”
Section: Determination Of Hearing Thresholdmentioning
confidence: 94%
“…These shortcomings of the automated ABR testing may be worsened if the intensity of the stimulus is not calibrated in the ear at the beginning of every test, leading to testing with higher stimulus intensities than intended. 18 An unexpected outcome of our screening procedure was the missed detection of infants with moderate or profound hearing loss by the automated ABR testing. In our study, 42% of the infants with hearing loss .45 dB HL passed the automated ABR test.…”
Section: Discussionmentioning
confidence: 99%